Placing Abstract Concepts in Space: Quantity, Time and Emotional Valence - Woodin, Greg; Winter, Bodo (Frontiers in Psychology, 2018)
Research has shown that abstract concepts are often conceptualised along horizontal and vertical axes. However, there are mixed results concerning which axis is preferred for which type of conceptual domain. For instance, it has been suggested that the vertical axis may be preferred for quantity in tasks using linguistic stimuli (e.g., ‘more’, ‘less’), whereas numerals (e.g., ‘1’, ‘2’, ‘3’) may be more prone to horizontal conceptualisation. In this study, we used a task with free response options to see where participants would place quantity words (‘most’, ‘more’, ‘less’, ‘least’), numerals (‘2’, ‘4’, ‘7’, ‘9’), time words (‘past’, ‘future’, ‘earliest’, ‘earlier’, ‘later’, ‘latest’) and emotional valence words (‘best’, ‘better’, ‘worse’, ‘worst’). We find that for quantity words, the vertical axis was preferred; whereas for numerals, participants preferred the horizontal axis. For time concepts, participants preferred the horizontal axis; and for emotional valence, they preferred the vertical axis. Across all tasks, participants tended to use specific axes (horizontal, vertical), rather than combining these two axes in diagonal responses. These results shed light on the spatial nature of abstract thought.